Frontispiece: Getting Ready for the Hydrogen Evolution Reaction: The Infrared Spectrum of Hydrated Aluminum Hydride–Hydroxide HAlOH+(H2O)n−1, n=9–14. Issue 31 (19th July 2021) - Heller, Jakob; Tang, Wai Kit; Cunningham, Ethan M.; Demissie, Ephrem G.; van der Linde, Christian; Lam, Wing Ka; Ončák, Milan; Siu, Chi‐Kit; Beyer, Martin K.
Abstract : Gas‐Phase Chemistry The infrared spectrum of hydrated aluminum hydride–hydroxide HAlOH + (H2 O) n −1 is reported in the Communication by Chi‐Kit Siu, Martin K. Beyer et al. on page 16858 .